What Architecture Students Learn About IoT and Energy Efficiency - Harsritanto, Bangun I.R.; Harani, Arnis Rochma; Riskiyanto, Resza; Wahyuningrum, Sri Hartuti (Journal of Information System and Informatics, 2025)
Energy consumption has become a major concern within academic communities, affecting everyone from undergraduate students to senior professors. In response, architectural schools in Indonesia have begun incorporating energy efficiency education into the curriculum for first-year students across various courses. One of the newest mandatory courses at the university is the Internet of Things (IoT). In the architecture department, this course not only covers the fundamentals of IoT but also emphasizes designing IoT solutions that support energy efficiency. This article describes the process by which architecture students integrate energy efficiency concepts into their IoT designs. A case study conducted during the Spring semester of 2025 in IoT classes for second-year students, using the updated teaching syllabus, highlights the positive outcomes. The results demonstrate that early-stage architectural education can significantly raise awareness of energy efficiency in both IoT and building design.